Perbedaan Terapi Murottal dan Pemberian Air Kelapa Muda Dalam Menurunkan Tekanan Darah Pada Klien Hipertensi - Ani Nuraeni (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2020)
Hypertension is a persistent increase in systemic blood pressure as indicated by a measurement of more than 140/90 mmHg. The multifactorial causes of hypertension are genetic, metabolic, and lifestyle behaviours such as diet, exercise, and stres. One selective approach to improve and control hypertension through complementary therapies such as Quran recitation therapy and green coconut water consumption was an alternative. The case study used descriptive methods to identify differences in blood pressure readings among selective high-risk hypertensive clients after attempted Quran recitation therapy and young coconut water intake. The case study subjects were four people with hypertension who treated with Quran recitation therapy, and a control group consumed green coconut water. The case study results showed a decrease in systolic and diastolic blood pressure after being given the intervention of Quran recitation and administration of young coconut water. The results of this case study recommend that further research with quasi-experimental methods and a larger number of respondents is needed to prove the effectiveness of the intervention of Quran recitation and the provision of young coconut water.